DETERMINAN KUALITAS LAPORAN KEUANGAN DESA PADA KECAMATAN LANGSA BARO - Mutia Sumarni (Program Studi Akuntansi, Fakultas Ekonomi. Universitas Samudra, 2024)
The aim is to determine the effect of education level, quality of training, work experience and office facilities on the quality of village financial statements in Langsa Baro sub-district. By using quantitative methods with a sample of 48 respondents. The sampling method in this study uses the census / total sampling method, this data analysis model uses multiple linear regression. The results of the study variable level of education have a positive and significant effect on the quality of village financial statements, variable quality of training has a positive and significant effect on the quality of village financial statements, variable of positive and significant work experience on the quality of village financial statements and variable facilities has a positive and significant effect on the quality of village financial statements while simultaneously the level of education, quality of training, Work experience and office facilities have a positive and significant effect on the quality of village financial statements .